Auction-theories critical chain approach for resource-constrained multi-project planning and scheduling - Shou, Yongyi. (2008)
The purpose of this research is to develop an effective technique for resource-constrained multi-project planning and scheduling. Though project management has developed for decades, most traditional network analysis techniques focus on time-only analysis and neglect resource constraints. Recently, a large volume of research has been conducted on resource-constrained project scheduling in the single project environment. However, there is relatively few research being conducted on the resource-constrained multi-project scheduling problems, though most projects are executed in a multi-project environment.